Integrasi Model Lean Sigma untuk Peningkatan Kualitas Produk - Pusporini, Pregiwati; Andesta, Deny (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
In order to develop business, the company has problems associated with waste. This research focuses on the incorporation of the concept of lean thinking and six sigma concept which is lean six sigma to improve quality. Lean six sigma tools which used in this study is Big Picture Mapping, Pareto Chart, Root Cause Analysis, Fishbone Diagram, and Failure Mode and Effect Analysis. Tools used above will support the improve stage to determine the priority of reprair. From the results found that 3 critically waste were defect, overproduction and inventory. Improve stage focus on the most critical waste issue is defect, primary process improvement method of paint, the process sequence and pre assy plug gage to measure eye reaming process. Waste overproduction and inventory focused on the Master Production Schedule (MPS). These improvements were expected to resolve issues relating to the elimination of defects, overproduction and inventory.